2012
DOI: 10.1039/c2nr30383c
|View full text |Cite
|
Sign up to set email alerts
|

Chitin nanofibers: preparations, modifications, and applications

Abstract: Chitin nanofibers are prepared from the exoskeletons of crabs and prawns by a simple mechanical treatment after the removal of proteins and minerals. The obtained nanofibers have fine nanofiber networks with a uniform width of approximately 10-20 nm and a high aspect ratio. The method used for chitin-nanofiber isolation is also successfully applied to the cell walls of mushrooms. They form a complex with glucans on the fiber surface. A grinder, a Star Burst atomization system, and a high speed blender are all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
237
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 415 publications
(241 citation statements)
references
References 77 publications
2
237
0
2
Order By: Relevance
“…For example, Ifuku et al reported a composite-type ChNF transparent paper fabricated by filtering a ChNF/water slurry obtained using a high-speed mechanical grinder. [36,37] Such a top-down approach is often combined with specific chemical treatments, such as TEMPO-mediated oxidation, to promote the individualization of ChNF. [38,39] Meanwhile, in a bottomup route, Zhang and co-workers recently demonstrated a pure chitin transparent paper fabricated by coagulating ChNF (regeneration) from a chitin solution dissolved in NaOH/urea/ water; [40] for this type of method nonaqueous solvent systems, such as LiCl/DMAc [41] and CaCl 2 /MeOH [42] are also available.…”
Section: Doi: 101002/adma201600336mentioning
confidence: 99%
“…For example, Ifuku et al reported a composite-type ChNF transparent paper fabricated by filtering a ChNF/water slurry obtained using a high-speed mechanical grinder. [36,37] Such a top-down approach is often combined with specific chemical treatments, such as TEMPO-mediated oxidation, to promote the individualization of ChNF. [38,39] Meanwhile, in a bottomup route, Zhang and co-workers recently demonstrated a pure chitin transparent paper fabricated by coagulating ChNF (regeneration) from a chitin solution dissolved in NaOH/urea/ water; [40] for this type of method nonaqueous solvent systems, such as LiCl/DMAc [41] and CaCl 2 /MeOH [42] are also available.…”
Section: Doi: 101002/adma201600336mentioning
confidence: 99%
“…Simple methods for preparing chitin nanofibers have recently been established [10,11,12]. In surface-deacetylated chitin nanofibers (SDACNFs), the nanofiber surface was transformed into chitosan by deacetylation while the core was maintained as a chitin crystal [13].…”
Section: Introductionmentioning
confidence: 99%
“…The most extensively studied one has been cellulose, the most abundant biomass on the globe (Edgar et al, 2001;Isogai, Saito, & Fukuzumi, 2011;Iwatake, Nogi, & Yano, 2008;Kim, Kim, Kang, Marquez, & Joo, 2006;Teramoto, Yoshioka, Shiraishi, & Nishio, 2002). Chitin and chitosan derived from Crustacea, the second most abundant biomass, have also been well studied (Ifuku et al, 2013;Ifuku & Saimoto, 2012). Their characteristics differ from those of other polysaccharides primarily because of the presence of acetamide and amino groups.…”
Section: Introductionmentioning
confidence: 98%